Religious literacy: Training on the women corpse management in Salam Village, Gebang District - Siti Khusniyati Sururiyah; Nur Hidayah; Riski Rahma Fitri; Annisa Ika Nur Aisyah (Universitas Muhammadiyah Magelang, 2023)
The law on the management of corpses is fardhu kifayah (collective obligation). However, the problem is that many people do not have the courage to do so, due to a lack of religious knowledge regarding burial of corpses, as well as fear of the corpse itself. The purpose of this community service is to provide knowledge and understanding of the simulation of handling women's corpse. This training was given twice, namely for PKK women and for members of Fatayat and Muslimat NU as pioneers of religious activities in Salam Village, Gebang District. The implementation method in this activity is Community-Based Participatory which is carried out collaboratively. The training materials provided include procedures for dealing with people in death throes, procedures for dealing with people who have recently died, procedures for washing the corpse, and ending with purification, procedures for shrouding the corpse, and the last reading the intentions and procedures for praying for a woman's corpse. From the results of the evaluation, the participants showed a positive response and were very enthusiastic about gaining new literacy knowledge about managing women's corpse according to Islamic law. As for the results of the feedback, a social team for the management of women's corpse will be formed in each RT.